Pengaruh Pemakaian Air Rendaman Sabut Kelapa Sebagai Penyiram Terhadap Pertumbuhan Seledri (Apium Graveolens) - Wendi Warisman Harefa (CV. SINAR HOWUHOWU, 2025)
This study aims to determine the effect of using coconut husk soaking water as a watering medium on the growth of celery plants (Apium graveolens). Coconut husk soaking water is known to contain various nutrients such as potassium, magnesium, and natural growth hormones that can support plant development. The research was conducted using an experimental method with a randomized block design (RBD), consisting of two main treatments: watering with plain water (control) and watering with coconut husk soaking water. Observed parameters included plant height, number of leaves, and leaf color over a specific growth period. The results showed that celery plants watered with coconut husk soaking water exhibited better growth compared to the control, particularly in terms of leaf number and greener leaf color. These findings indicate that coconut husk soaking water has the potential to serve as a natural watering alternative that can enhance soil fertility and the quality of celery plant growth. Thus, utilizing coconut husk waste in the form of soaking water can be an environmentally friendly solution for sustainable agricultural practices.